Pengaruh Kualitas Produk Dan Gaya Hidup Terhadap Keputusan Pembelian Iphone di Bandar Lampung - Muhammad William; Iskandar Ali Alam; Nuris Sanida (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The study want to knows the effects from product quality and lifetstyle on iPhone purchasing decision in Bandar Lampung, where the iPhone is known a symbol of social status and modern lifestyle. This survey includes quantitative approach method with multiple linear regression analyis. The information were obtained from 100 iPhone user respondents by an online questionnaire and then evaluation through the SPSS version 30 for windows program. The result from this research show that product quality and lifestyle partially and simultaneously affect iPhone purchasing decisions in Bandar Lampung. This research provides a new perspective regarding the factors that cause7 iPhone purchasing decisions that emphasize the important role of product quality and lifestyle in the context of an envolving market.